Stalinism and the Soviet-Finnish war of 1939-40: crisis management, censorship and control - Spencer, M (2015)
In both western and Russian historiography the Soviet-Finnish War of 1939-40 enjoys, at best, only a passing reference in any narrative of the period and is poorly integrated into existing scholarly analyses of the Soviet regime under Stalin. It is my contention that this conflict offers an invaluable opportunity to test for continuity and change in the form and function of the Stalinist system. Between the disastrous efforts of its forces and the condemnation of the international community, the Kremlin was confronted with the serious challenge of how to portray the events of the war in the media, while managing domestic and international opinion over the course of the fighting. This thesis examines the extent to which the Soviet regime under Stalin had the institutions and agents in place at the close of the 1930s to cope with the crisis of war in Finland; to be in command of the military campaign, while simultaneously controlling the direction of the official narrative about the fighting; and to censor conflicting interpretations, experiences and information channels, which might expose the Red Army's woeful performance on Finnish territory. This mobilisation of press, propaganda and censorship organs in the face of widespread international condemnation and domestic disquiet constituted a significant challenge for a regime still dealing with the sudden reorientation of the Communist International, required after the Soviet Union’s conclusion of a non-aggression treat with Nazi Germany in August 1939. An international perspective is central to this thesis, with a view towards assessing the strengths and weaknesses of the public face and private practice of Soviet information controls.